Diagnosis and Treatment of Endometriosis. Guideline of the DGGG, SGGG and OEGGG (S2k Level, AWMF Registry Number 015/045, August 2020) - Burghaus, Stefanie; Schäfer, Sebastian D.; Beckmann, Matthias W.; Brandes, Iris; Brünahl, Christian; Chvatal, Radek; Drahoňovský, Jan; Dudek, Wojciech; Ebert, Andreas D.; Fahlbusch, Christine; Fehm, Tanja; Fehr, Peter Martin; Hack, Carolin C.; Häuser, Winfried; Hancke, Katharina; Heinecke, Volker; Horn, Lars-Christian; Houbois, Christian; Klapp, Christine; Kramer, Heike; Krentel, Harald; Langrehr, Jan; Matuschewski, Heike; Mayer, Ines; Mechsner, Sylvia; Müller, Andreas; Müller, Armelle; Müller, Michael; Oppelt, Peter; Papathemelis, Thomas; Renner, Stefan P.; Schmidt, Dietmar; Schüring, Andreas; Schweppe, Karl-Werner; Seeber, Beata; Siedentopf, Friederike; Sirbu, Horia; Soeffge, Daniela; Weidner, Kerstin; Zraik, Isabella; Ulrich, Uwe Andreas (Geburtshilfe und Frauenheilkunde, 2021)
Aims The aim of this official guideline published and coordinated by the German Society of Gynaecology and Obstetrics (DGGG) in cooperation with the Austrian Society for Gynaecology and Obstetrics (OEGGG) and the Swiss Society for Gynaecology and Obstetrics (SGGG) was to provide consensus-based recommendations for the diagnosis and treatment of endometriosis based on an evaluation of the relevant literature.Methods This S2k guideline represents the structured consensus of a representative panel of experts with different professional backgrounds commissioned by the Guideline Committee of the DGGG, OEGGG and SGGG.Recommendations Recommendations on the epidemiology, aetiology, classification, symptomatology, diagnosis and treatment of endometriosis are given and special situations are discussed.Ziel Das Ziel dieser offiziellen Leitlinie, die von der Deutschen Gesellschaft für Gynäkologie und Geburtshilfe (DGGG), der Österreichischen Gesellschaft für Gynäkologie und Geburtshilfe (OEGGG) und der Schweizer Gesellschaft für Gynäkologie und Geburtshilfe (SGGG) publiziert und koordiniert wurde, ist es, durch die Evaluation der relevanten Literatur einen konsensbasierten Überblick über die Diagnostik und Therapie der Endometriose zu geben.Methoden Diese S2k-Leitlinie wurde durch einen strukturierten Konsens von repräsentativen Mitgliedern verschiedener Professionen im Auftrag der Leitlinienkommission der DGGG, OEGGG und SGGG entwickelt.Empfehlungen Es werden Empfehlungen zur Epidemiologie, Ätiologie, Klassifikation, Symptomatik, Diagnostik und Therapie der Endometriose gegeben und spezielle Situationen diskutiert.
Keywords: endometriosis; diagnosis; treatment; pelvic pain; guideline